Assessment of Water Balance for Russian Subcatchment of Western Dvina River Using SWAT Model - Terskii, Pavel; Kuleshov, Alexey; Chalov, Sergey; Terskaia, Anna; Belyakova, Pelagiya; Karthe, Daniel; Pluntke, Thomas (Frontiers in Earth Science, 2019)
The study provides a new assessment of the water balance components of the catchment (evapotranspiration, surface and lateral flow etc. and its spatial distribution and temporal variability) for the transboundary catchment of Western Dvina river within the poorly gauged Russian part of the catchment.The study focuses on modeling the inland flow generation processes using open source data and the SWAT (Soil Water Assessment Tool) hydrological model. The high interannual variability of river flow and impact of snowmelt processes were especially taken into account when setting up the model and processing the calibration. The database of daily meteorological data for the period 1981 – 2016 was prepared using global atmospheric reanalysis ERA-Interim data and observed station data from the GSOD NCDC/NOAA and ECA&D datasets. The considered datasets were tested on plausibility and regionalized. The catchment model was built on the basis of open land use / land cover (LULC) data sets, topography and soil, so that the entire transboundary catchment area could be easily implemented in the next step. For the daily model calibration, 19 sensitive parameters were chosen manually. The most sensitive are the parameters which consider snow melting processes and flow recession curve number. The highest impact on water balance components has the area and distribution of wetlands. Lakes strongly affect the evapotranspiration rate. The study provides further research with uncertainty analysis and recommendations for model improvement and model limitations. The developed modelling approach can be used to assess water resources, climate change impacts, and water quality issues in comparable regions.